Voiceless Idols, Speaking People: 1 Corinthians 12–14 and the Accessibility of Divine Presence - Thomson, Ambrose (Journal for the study of Paul and his letters, 2020)
There is a broad consensus in New Testament scholarship that 1 Cor 12-14 is Paul’s attempt to reign in an abusing use of glossolalia among the Corinthian Christ followers. While a concern about such abuse is evident in the passage, the extent of Paul’s discussion, particularly in its theologically reflective character, is rather more complex than typical treatments of this passage recognize. This article sets forth a fresh reading of 1 Cor 12-14 that takes as its starting point the framing statements of 1 Cor 12:1-3 as an essentially Jewish theological formulation. I argue that Paul’s entire discussion in 1 Cor 12-14 hangs on an Old Testament theological framework that specifically addresses the problem of access to divine presence in terms that are culturally relevant to the ancient world. A coherent description of what Paul is actually saying about a proper understanding and use of spiritual “gifts” is then developed from this framework. The resulting thrust of the passage is that universal and equal access to the presence of God is the hallmark of the redeemed community, which thereby has the responsibility of making God’s presence available, accessible, and efficacious to others.